The Positive Politeness Strategies Used in “English for Nusantara” Textbook - Rita Erlinda; Herick Afrinursalim; Fadhil Dinarta (Yayasan Visi Intan Permata, 2023)
The integration of pragmatic competence and politeness is an essential focus in the development of English learning materials like textbooks. Using appropriate textbooks can help students develop communicative competence as the primary goal of English language teaching as a foreign language. This study discusses the positive politeness strategy in the textbook